BANK CREDIT, CREDIT RISKAND FARM PRODUCE - Muyanja Ssenyonga (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2004)
The research investigates the determinants and impact of bank credit on output in the food crops and fisheries sub sectors; whether or not there is a significant difference in the risk on bank credit and output in the two sub sectors, and whether or not there is a relationship between risk obtaining in the two sub sectors. The results indicate the positive and significant influence of bank credit on food crops output, but a positive and insignificant influence on fisheries output, which unequivocally vindicates government intervention in credit disbursement to agriculture. The influence of banking deregulation on bank credit supply is shown to differ between the two sub sectors, for while it registers expected positive sign in the fisheries sub sector, it produces negative and insignificant influence in the food crops sub sector. Bank reserve requirements has a negative influence on bank credit extended to the fisheries sub sector, while it induces a positive and significant influence in the food crops sub sector. The 1997 economic crisis causes an autonomous contraction of bank credit to the food crops sub sector, but accentuates it in the fisheries sub sector. The food crops and fisheries sub sectors register significant influence of rate of interest rate on bank credit on bank credit supply. Obstacles to credit disbursement to the two sub sectors are presented, followed by policy implications deemed necessary to improve the credit situation in the agricultural sector.